SOME CONSIDERATIONS ON THE TYPOLOGY OF PHILOSOPHICAL-ANTHROPOLOGICAL MODELS (TO THE PROBLEM OF VALUE IDENTIFICATIONS OF UKRAINIANS) - V. V. Mudrakov; O. S. Polishchuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article deals with the consideration of certain types of value models of human creation from the standpoint of philosophical anthropology and social philosophy. It is about certain models that fulfill the worldview-semantic modes of a person. Theoretical basis. The authors cover (O. Polishchuk – Thesis I; V. Mudrakov – Thesis II) peculiarities of such models in the process of creation of "the new types of a person". The process of reformatting these types and its means are studied. The process of valuing metamorphoses of Ukrainians is taken as an example. The research is limited to the Soviet period and the period of independence, which is reflected respectively in Thesis I – The Phenomenon of Homo Sovieticus and Thesis II – A Person in the Situation of Post-Homo Sovieticus. The emphasis is on the peculiarities of the value matrix of these types and their ideological potential. Originality is in the disclosure of anthropological models that correspond to the value functionality, that is, the determination and expression of the essence of a person. It is shown that certain projects, under the conditions of forced reformatting, by their value reduction are classified as inhuman. They are based on the narrative of ideological myth and deprived of the projection of the complete development of a personality. The proposed approach allows to revise the current trends of such projections and, most importantly, to predict their value potentials in the dynamics of the transformational progress of the essence of the modern Ukrainian. Conclusions. The essay reflects the process of transformation of the worldview-semantic modes, which are represented by two situations-products – the Soviet person and the contemporary. The first type is formed by the mythology of political ideology. This person is deprived of himself or herself. Their collective identity is brought up by the anthropological effect of violence and fear. The second type is very similar. This person finds himself or herself in the situation of value disorientation, nostalgic impulses and instrumental thinking. Their task is to move towards the "monad personality". This is possible by means of formation of the "own philosophy", "inherent teleology of a breakthrough", as well as by taking into account the problem of consolidation and radicalism of external factor.